2009
DOI: 10.1097/mph.0b013e3181bc9c85
|View full text |Cite
|
Sign up to set email alerts
|

Karyotyping, FISH, and PCR in Acute Lymphoblastic Leukemia

Abstract: Diagnostic accuracy of tests for detecting t(9;22), t(12;21), and t(11q23) is generally high, although sensitivity is not optimal for all anomalies. Despite the high-diagnostic accuracy, all diagnostic techniques should be used complementary, because any detection of a (significant) chromosomal aberration irrespective of diagnostic mode has to be considered in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…As expected, FISH is of benefit in the detection of ETV6 and CDKN2A rearrangements, since these rearrangements are cytogenetically cryptic and invisible. On the other hand, the sensitivity of G-banded karyotype for the detection of BCR/ABL1 and MLL rearrangements in ALL is relatively high (80% and 85%, respectively) [17]. Consistent with previous studies, our study showed that in ALL, ETV6 and CDKN2A genetic abnormalities, which were not identified by G-banded karyotype, could be additionally detected by FISH (28% and 33%, respectively).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, FISH is of benefit in the detection of ETV6 and CDKN2A rearrangements, since these rearrangements are cytogenetically cryptic and invisible. On the other hand, the sensitivity of G-banded karyotype for the detection of BCR/ABL1 and MLL rearrangements in ALL is relatively high (80% and 85%, respectively) [17]. Consistent with previous studies, our study showed that in ALL, ETV6 and CDKN2A genetic abnormalities, which were not identified by G-banded karyotype, could be additionally detected by FISH (28% and 33%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…One study showed that ALL FISH profile tests revealed additional genetic aberrations not detected by G-banded karyotype in up to 49% of cases, and among these, ETV6/RUNX1 ( TEL/AML1 ) abnormalities were frequently detected (44%), followed by the abnormal CDKN2A (25%) and hyperdiploidy (18%) [4]. A further study also demonstrated that G-banded karyotype failed to detect a considerable part of the ETV6/RUNX1 ( TEL/AML1 ) translocation (sensitivity 6%) [17]. As expected, FISH is of benefit in the detection of ETV6 and CDKN2A rearrangements, since these rearrangements are cytogenetically cryptic and invisible.…”
Section: Discussionmentioning
confidence: 99%
“…It shows, as in the case of previous reports [Soszynska et al, 2008;Olde Nordkamp et al, 2009;Harrison et al, 2010], that the detection of CAs using conventional cytogenetics is distinctly improved by FISH and/or RT-PCR methods. These techniques should be used simultaneously to improve accuracy in the identification of the main CAs, since they are useful tools with diagnostic and prognostic value in the management of children with ALL.…”
Section: Discussionsupporting
confidence: 60%
“…Unlike karyotyping, which provides a view of the whole genome of a cell, qPCR and FISH-based methods are target specific and hence typically serve as complementary analyses to genome-wide methods (Gekas et al., 2011, Olde Nordkamp et al., 2009). D'Hulst et al.…”
Section: Introductionmentioning
confidence: 99%